FACTORS ASSOCIATED WITH PREVENTABLE SEVERE EXTRAPYRAMIDAL SYMPTOMS FROM ANTIPSYCHOTIC USE IDENTIFIED USING BENZTROPINE AS A TRIGGER TOOL - Chongpornchai, Jongkonnee; Tanchakvaranont, Sitthinant (Thai Bulletin of Pharmaceutical Sciences, 2025)
Preventable adverse drug events (ADEs) are critical targets for detection to ensure patient safety. This study aimed to evaluate factors associated with the occurrence of preventable ADEs among patients receiving benztropine, used as a trigger tool for monitoring severe extrapyramidal symptoms in patients treated with antipsychotics. A retrospective study was conducted by reviewing patient medical records at Saraburi Hospital. The population comprised all patients who received benztropine at Saraburi Hospital between October 1, 2021, and September 30, 2024. The sample included those who met the inclusion criteria of receiving antipsychotics and assessing ADEs, excluding cases with incomplete, abnormal, or implausible data. Collected data included patient demographic characteristics and clinical data. Data were analyzed using descriptive statistics, and the associations between variables were examined using the chi-square test or fisher’s exact test, as appropriate. Subsequently, univariate binary logistic regression was performed to assess the factors affected with the occurrence of preventable and non-preventable ADEs. The univariate analysis of 62 patients, of whom 38 experienced preventable ADEs, most factors were not significantly associated with the occurrence of preventable ADEs. However, the duration of antipsychotic use showed a statistically significant association with the occurrence of preventable ADEs (p-value = 0.017). Patients who had received antipsychotic treatment for more than 4 months were approximately 5.83 times more likely to experience preventable ADEs compared with those who had received treatment for 4 months or less (OR = 5.833). The findings indicated that prolonged use of antipsychotics for more than 4 months was associated with preventable ADEs. Therefore, regular monitoring and risk assessment should be implemented, along with the development of pharmacovigilance systems, to prevent such events in this patient group.